(untitled) (Texas Journal of Medical Science, 2025)
Obesity and metabolic syndrome (MS) are significant risk factors for cardiovascular and endocrine diseases among young people. The purpose of the study is to assess metric indicators, the prevalence of body mass disorders, and potential risk factors for MS among students. The study involved 382 students of the Central Asian Medical University (Fergana city, Uzbekistan) aged 18-25. An assessment of height, waist circumference (WC), body mass index (BMI) was conducted, and the distribution of students by BMI categories was calculated. It was established that 21.8% of students have a metabolic risk, of which 23.8% have excess body weight and 1.6% have obesity of the 1st degree. The average BMI value was 23.8±2.1 kg/m2. The results obtained confirm the necessity of implementing preventive programs aimed at reducing the prevalence of obesity risk factors among university students